I LIVE NOT I BUT CHRIST LIVES IN ME: PAUL’S CHRIST EXPERIENCE FROM A YOGIC PERSPECTIVE - Thelakkadan, Paulcy (Asian Horizons, 2016)
Paul, a zealous Pharisee and an erstwhile persecutor of the Church, turned to be the Apostle of the Gentiles, lived a life of mystical union with Christ ever since his encounter with Christ on the way to Damascus. It brought about a real transformation in his life in such a manner that he stated that it was no longer he who lived, but Christ in him. His actions, knowledge and devotion were fused into a new relationship with Christ through which he allowed Christ to live and act through him. This was a mystical experience of personal union with Christ, which can be characterized in the Indian spiritual terminology as Yoga, which originally and etymologically means union.